Mathematics teaching module design with tri-n (niteni, nirokke, nambahi) with problem based learning model - Sutanto, Sutanto; Riyantini, Atik; Irfan, Muhammad (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2024)
This research aimed to develop fourth-grade elementary school students’ integration of learning with problem-based learning and the teachings of Ki Hadjar Dewantara Tri-N (Niteni, Nirokke, Nambahi). This research is research and development with the PPE development model which consists of three stages, namely Planning (Planning), Production (Product Preparation), and Evaluation (Evaluation). This research was conducted at Ngentak Sanden Elementary School, Bantul Regency in Grade IV mathematics subjects. The data collection instrument uses an assessment sheet of mathematics teaching modules that have been validated by experts (expert judgment). The data collection technique in this study used product validity tests. The initial step of this research is to convert qualitative data from the results of expert assessment, material and media into quantitative data forms. The next step is to calculate the actual score and the average of the actual score. Quantitative data in the form of average actual scores are then converted into qualitative data using the Likert scale. The results of validation by material and media experts, the module is said to be valid with an average actual score of 98.5 with good criteria and 51.7 with Very Good criteria. The results of this study are expected to provide benefits for students in learning to improve mathematical reasoning. This research was successfully carried out by designing and developing a mathematics teaching module with a problem-based learning model based on Tri-N (Niteni, Nirokke, Nambahi) in a Grade IV Elementary School.